Adsorption of Rare Earth Elements (REEs) onto Activated Carbon Modified with Potassium Permanganate (KMnO4) - Kano, Naoki; Pang, Meiling; Deng, Yanling; Imaizumi, Hiroshi (Journal of Applied Solution Chemistry and Modeling, 2017)
The adsorption capacity of activated carbon modified with potassium permanganate (KMnO4) for rare earth elements (REEs) from aqueous solution was investigated. The modified activated carbon was characterized by SEM (scanning electron microscopy), FT-IR (Fourier transform infrared spectrometer), and N2 adsorption-desorption tests. Adsorption experiments from aqueous solutions containing known amounts of some REEs (i.e. La, Lu, Yb, Eu, Y, Sc) onto the carbon were explored in a batch system. The amount of REEs adsorbed at different pH values, initial concentrations, and contact times were determined by inductively coupled plasma-atomic emission spectrometry (ICP-AES) in order to determine the optimum conditions for REEs adsorption. The adsorption of REEs on the activated carbon was well fitted by the Langmuir isothermal adsorption equation. The rates of adsorption were found to conform to pseudo-second order kinetic. These results present the modified activated carbon as an efficient adsorbent for REEs, hence creating new avenues for the treatment of industrial waste waters including pollutants. It is very significant information from the viewpoint of environmental protection.